2015
DOI: 10.2807/1560-7917.es2015.20.14.21086
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the HIV epidemic among men who have sex with men in the United Kingdom, 1999–2013

Abstract: We describe epidemiological trends in HIV among men who have sex with men (MSM) in the United Kingdom (UK) to inform prevention strategies. National HIV surveillance data were analysed for trends. Multivariable analyses identified predictors of late diagnosis (<350 copies/µL) and mortality. Between 1999 and 2013, 37,560 MSM (≥15 years) were diagnosed with HIV in the UK. New diagnoses rose annually from 1,440 in 1999 to 3,250 in 2013. The majority of MSM were of white ethnicity (85%) and UK-born (68%). Media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 18 publications
1
25
1
Order By: Relevance
“…Our data are also congruent with surveillance data which show a significant year-on-year increase in new UK HIV diagnoses among Asian and black African men for over a decade 8. Other data point to the importance of mental health.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our data are also congruent with surveillance data which show a significant year-on-year increase in new UK HIV diagnoses among Asian and black African men for over a decade 8. Other data point to the importance of mental health.…”
Section: Discussionsupporting
confidence: 88%
“…In recent years, HIV prevention policy and practice among GBM in the UK has concentrated on increasing HIV testing. Between 1999 and 2013, the number of HIV tests taken by GBM in the UK increased almost 10-fold (from 10 900 to 102 600) and the number of new diagnoses more than doubled (1440–3250) over the same period 8. There is no data available about the differential impact of these changes on different ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…34 In the United Kingdom, new HIV diagnoses among MSM rose annually from 1440 in 1999 to 3250 in 2013. 35 The ITACA cohort of 3544 MSM established in Barcelona, Spain, noted an overall HIV incidence of 2.4 per 100 person-years, with foreign born men being at increased risk for infection. 157 During the study period, HIV incidence increased from 1.2 to 3.1 person-years from 2009 to 2011.…”
Section: Current Hiv Incidence Data Among Men Who Have Sex With Men Imentioning
confidence: 99%
“…50 In the UK, the largest increases in new HIV diagnoses from 1999 to 2013 occurred among young MSM aged 15-24 years (16% of new diagnoses). 35 HIV incidence The Centers for Disease Control and Prevention (CDC) estimated, using data from 2009 to 2013, that one in two Black MSM and one in four Hispanic MSM will be diagnosed with HIV in their lifetime, compared with 1 in 11 White MSM and 1 in 132 White men. 56 In a cohort study of young MSM in Chicago, the highest incident rate recorded was among young Black MSM, with an incidence of 6.2 infections per 100 person-years compared with 2.9 infections per 100 person-years among Hispanic young MSM and 0.9 infections per 100 person-years among young White MSM in the same cohort.…”
Section: Hiv Incidence Among Young Msmmentioning
confidence: 99%
“…Similarly, a national survey of MSM living in Britain found that BSA were more likely to express anxiety about attending a sexual health clinic due to the possibility that others in their community might find out that they had sex with men (McKeown et al, 2012). Although the prevalence of diagnosed HIV remains low among South Asians in the UK, a year on year increase in HIV incidence has been observed in this group (Desai et al, 2015). Given the scarcity of research among BSA MSM, this study explores the factors likely to be associated with sexual risk-taking in this group.…”
Section: Introductionmentioning
confidence: 99%